Analyzing Students' Learning Styles: Visual, Auditory, Kinesthetic - Anisa Pitri; Tessa Imelda; Wamai Syarah; Reza Arridho; Yan Fahmi Zuher; Dafrizal Dafrizal; Munawir K; Mutathahirin Mutathahirin; Pioni Nurhaliza (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2025)
Learning styles in students are considered very important for the learning process and learning outcomes. In implementing the learning process, we as educators must be creative and enjoyable. Before that, tests, observations, and interviews need to be conducted with each student. The purpose of this article's research is to find out what learning styles are preferred by students majoring in fashion design. The method used in this study was descriptive research in the form of a questionnaire for fashion design students, which contained several questions related to learning styles. Twenty students completed the questionnaire, and the results showed that the majority had auditory and visual learning styles. Only a few students had kinesthetic learning styles.